Juvenile Criminal Responsibility in Justice Systems: A Comparative Study of Judicial Interpretations in Indonesia and Australia - Muchtar, Syamsuddin; Irwansyah, Irwansyah; Yunus, Ahsan; Pratiwi Arifin, Arnita; Faried, Markham (Jambe Law Journal, 2024)
This study explores the intersection balance between legal frameworks and customary obligations in the imposition of additional punishment by judges, particularly in the context of juvenile justice in Indonesia. As a normative-legal research, this study employs philosophical, theoretical, and conceptual approaches to examine how juvenile criminal justice systems of Indonesia and Australia, with focus on the Provinces of Bali and West Papua, where indigenous and local knowledge play a significant role in shaping judicial decisions. The findings reveal that Indonesian judges incorporate theological, sociological, and legal considerations when determining juvenile criminal responsibility. By blending community norms with legal principles, they aim to ensure justice that aligns with societal values. This approach underscores the significance of harmonizing legal decisions with local cultural expectations, fostering a restorative justice model that prioritizes rehabilitation over punishment. In contrast, Australia’s juvenile justice system emphasizes formal legal procedures and rehabilitation but does not integrate local cultural norms as extensively as Indonesia. By comparing these two systems, the study provides valuable insights into how legal frameworks can adapt to diverse cultural contexts while upholding universal principles of justice. This research enriches the global discourse on juvenile justice, highlighting Indonesia's experience as a compelling example of a legal system striving for justice through a culturally sensitive and restorative approach.